Comparison of economic analysis between self-conducting or hired contractor for FFB transportation from infield to ramp / Mohammad Azzam Tohid - Tohid, Mohammad Azzam (Faculty of Plantation and Agrotechnology, 2017)
One of the problems faced in the oil palm plantation management is to choose the type of management to reduce their expenditure cost in transporting fresh fruit bunch (FFB) out from the field to ramp. The estate management or smallholder will need to choose either having their own transport (self-conducting) or hired contractor to reduce their operational cost in transporting of FFB to the ramp. The objective of this research is to study the cost of two different management systems, revenue, determine the lowest cost and to compare the different transporting system affecting the tonnage of FFB. In this study, the data collected was secondary data type and interview with the supervisor and assistance manager from Ladang at Kota Tinggi, Johor for hired contractor and Pineapple Cannery at Pontian, Johor for self-conducting. The types of data collected include yield in tonnage, labor, operating cost, price, etc. The data collected were analyze by using Microsoft excel and t-test using software SPSS 20.0. From the result, it was shown that is no significance difference in the average revenue between the two systems. It is because every system either by self-conducting or hired contractor have same target which is to maximize profit. The results, they will do their work properly and follow timelines to ensure all FFB are transported on time to avoid delay evacuated to the mill and cause FFA rate increase.